2022
DOI: 10.3389/fcvm.2022.843606
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation of Initial Ambrisentan Plus Phosphodiesterase Type 5 Inhibitor on Right Ventricular Pulmonary Artery Coupling in Severe Pulmonary Arterial Hypertension Patients

Abstract: Introductionambrisentan and phosphodiesterase type 5 inhibitor (PDE5i) have been approved for treating patients with pulmonary arterial hypertension (PAH). Echocardiographic right ventricular pulmonary artery coupling (RVPAC) has been shown to be a valid non-invasive and alternative measurement method to assess the predicted outcomes in PAH patients. The aim of this study was to study the effect and clinical correlates of initial ambrisentan plus PDE5i combination therapy on RVPAC in patients with severe PAH.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Although right ventricular diameter and TAPSE improved significantly, the trend in decreasing RA area did not reach statistical significance. Several other studies have also demonstrated that changes in right heart structure and function lagged behind NT-proBNP levels and exercise ability (24,25). A recently published meta-analysis indicates that the improvement in RV systolic function appeared as long as 6 months and in the right atrial area, 12 months, after initiation of targeted therapy in PAH patients (26).…”
Section: Discussionmentioning
confidence: 97%
“…Although right ventricular diameter and TAPSE improved significantly, the trend in decreasing RA area did not reach statistical significance. Several other studies have also demonstrated that changes in right heart structure and function lagged behind NT-proBNP levels and exercise ability (24,25). A recently published meta-analysis indicates that the improvement in RV systolic function appeared as long as 6 months and in the right atrial area, 12 months, after initiation of targeted therapy in PAH patients (26).…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have revealed that NT-proBNP shows a faster response to PAH-specific therapies than that of other measurements of cardiac function (such as RV contractility and RV end-diastolic volume). [21–24] This phenomenon suggests that an adequate treatment duration of PAH-specific therapy may lead to better outcomes in patients with PAH during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In all 85 patients, C-section was performed, with only 9.4% of which performed for therapeutic abortion. Compared with the untreated group, the treated group comprised older individuals (31 [26, 33] years vs. 27 [24,31] years; P = 0.029) with higher sPAP (98 [78, 105] mm Hg vs. 73 [59, 88] mm Hg; P < 0.001) and larger RV diameter (32 [27, 37] mm vs. 28 [23,33] mm; P = 0.010). Although no significant difference was detected, the treated group comprised a higher proportion of patients under general anesthesia and those classified as WHO-FC III/IV (worse cardiac FC).…”
Section: Baseline Characteristicsmentioning
confidence: 99%